Reflective practitioners in the 21st century: a framework for ongoing teacher professional development - Jacquard, Marie Dianne (2013)
As a Reading Recovery Teacher Leader, it was possible to study a group of teachers learning to teach Reading Recovery. It was observed that not only did the teachers eyes open to the possibilities of student learning, but also to their own learning. With this in mind, the focus of this study is to follow a group of three teachers who are transforming their learning during the 2008-2009 academic year. Parallel to their learning, a new theory of offering professional development will be explored, that could be employed beyond the confines of Reading Recovery.